Cariprazine augmentation in patients with treatment resistant unipolar depression who failed to respond to previous atypical antipsychotic add-on. A case-series - Pessina, Enrico; Martini, Azzurra; Raffone, Fabiola; Martiadis, Vassilis (Frontiers in Psychiatry, 2023)
Among individuals receiving an adequate pharmacological treatment for Major Depressive Disorder (MDD), only 30% reach a full symptom recovery. After an inadequate response to an antidepressant, possible next step options include augmenting antidepressant with a non-antidepressant medication, most evidence-based support use of atypical antipsychotics (AAs). Few data are available in literature about switching to another antipsychotic when a first augmentation trial has failed. We present a case-series of ten patients with unipolar treatment resistant depression who were treated with a combination of antidepressant and low dose of cariprazine after failing to respond to a first augmentation with another AA All patients failed to respond to conventional antidepressant therapy and to a first trial with a low dose of AA. A second augmentation trial was then made with cariprazine. Seven out of ten patients were responders at the end of period. HAM-D mean scores decreased from 23.9 ±3.9 (baseline) to 14.8 ±5.3 (4 weeks). Cariprazine was well tolerated, no severe side effect was observed during the trial. Our sample of treatment resistant unipolar patients showed good response to augmentation with cariprazine. Failure to a first AA-augmentation trial does not preclude response to a second one. This preliminary result requires confirmation through more rigorous studies conducted over greater samples. occupational outcomes